Impact of delayed addition of PD-1/PD-L1 inhibitors to chemotherapy on outcomes in patients with extensive-stage small cell lung cancer - Shuangqing Lu; Chao Wang; Xiaoyang Zhai; Zhuoran Sun; Ke Zhao; Dawei Chen; Hui Zhu (Therapeutic Advances in Medical Oncology)
Background: Immunotherapy combined with chemotherapy is the first-line treatment for extensive-stage small cell lung cancer (ES-SCLC). However, the effect of delayed initiation of immunotherapy on its efficacy remains unclear. Objectives: This study aimed to investigate the impact of the delayed addition of programmed death receptor 1/programmed death ligand 1 (PD-1/PD-L1) inhibitors on treatment outcomes in patients with ES-SCLC. Design: This retrospective cohort study used propensity score matching (PSM) to balance baseline characteristics. Methods: This study included 416 patients with ES-SCLC who received first-line immunotherapy between January 2020 and December 2022. Patients were categorized into two groups: delayed-immunotherapy (IO) (PD-1/PD-L1 inhibitors initiated during the 2nd or 3rd chemotherapy cycle) and early-IO (immunotherapy initiated during the first cycle). A 1:1 PSM was performed to balance baseline characteristics. The primary endpoints were overall survival (OS) and progression-free survival (PFS), which were analyzed using the Kaplan-Meier method and compared using log-rank tests. Results: Owing to the exclusion of PD-L1/PD-1 inhibitors from medical insurance, financial constraints, and poor physical condition of some patients, 72 patients were included in the delayed-IO group (second cycle: 41; third cycle: 31), while 344 were in the early-IO group. Before PSM, median OS and PFS in the delayed-IO group were 24.00 and 8.75 months, compared to 18.59 and 7.57 months in the early-IO group, with no significant differences (OS: HR 0.72, p  = 0.054; PFS: HR 0.86, p  = 0.281). After PSM (72 patients per group), the delayed-IO group showed significantly longer median OS (24.00 vs 18.79 months, HR 0.60, 95% CI 0.38–0.97, p  = 0.037) and PFS (8.75 vs 6.49 months, HR 0.69, 95% CI 0.48–0.99, p  = 0.044) compared to the early-IO group. These results suggest that, in specific patient populations, delayed immunotherapy may improve survival outcomes by optimizing patient condition or treatment response. Conclusion: In patients with ES-SCLC, delayed administration of PD-1/PD-L1 inhibitors during the second to fourth chemotherapy cycles improves survival outcomes compared to concurrent administration during the first cycle, with a similar safety profile. These results suggest that, in specific patient populations, delayed immunotherapy may improve survival outcomes by optimizing patient condition or treatment response.